Development of palliative care and legalisation of euthanasia: antagonism or synergy?. Issue 7649 (17th April 2008) - Bernheim, Jan L; Deschepper, Reginald; Distelmans, Wim; Mullie, Arsène; Bilsen, Johan; Deliens, Luc
Abstract : Debates about euthanasia often polarise opinion, but Jan Bernheim and colleagues describe how in Belgium the two camps grew up side by side to mutual benefit